The impact of livelihood capital on the social integration of relocated households: mediating effects based on livelihood risk - Zhao, Chuangxin; Tang, Manping; Wang, Changxiang (Frontiers in Sustainable Food Systems, 2025)
The social integration of relocated migrants directly determines the success or failure of poverty alleviation relocation efforts. This paper aims to explore the impact of livelihood capital on the social integration of relocated households and the underlying mechanisms. Based on the sustainable livelihoods framework, the Ordinary Least Squares (OLS) model, quantile regression model, and mediation analysis are used to investigate the relationships between livelihood capital, livelihood risk, and the social integration of relocated households, using 610 survey responses from relocated poverty alleviation households in China collected in 2024. The results are as follows: (1) Overall, livelihood capital has a significant positive effect on the social integration of relocated households. For every one-unit increase in livelihood capital, the social integration level of relocated households increases by 55.32%. However, as the level of social integration improves, the effect of livelihood capital on social integration gradually diminishes. (2) The livelihood risk of relocated households plays a partial mediating role in the process through which livelihood capital affects social integration. In terms of sub-dimensions, environmental risk, employment risk, and health risk each play a partial mediating role in this process. (3) Further analysis reveals that livelihood capital has a more significant positive effect on the social integration of relocated households in township resettlements, part-time agricultural livelihoods, and female-headed households compared to urban resettlements, non-agricultural households, and male-headed households. Based on these findings, the government should focus on improving the livelihood capital of relocated households in multiple dimensions, design and implement multi-layered risk management strategies, and adopt differentiated policies tailored to the specific circumstances and needs of each group to promote the social integration of relocated households.